Comparative Evaluation of Effectiveness of Demineralized Freeze-dried Bone Allograft and Other Regenerative Materials for the Treatment of Intrabony Periodontal Defects: A Systematic Review and Meta-analysis - Mayuri Rajiv Ghike; Mangesh Bhalchandra Phadnaik; Vaibhav Karemore; Yugandhara Rameshsingh Desurkar (Journal of Head & Neck Physicians and Surgeons)
The aim of this systematic review and meta-analysis is to evaluate and compare the effectiveness of demineralized freeze-dried bone allograft (DFDBA) and other regenerative materials for the treatment of intrabony periodontal defects. Randomized controlled trials (RCTs) and non-randomized controlled trials (Non-RCTs) reporting on clinical and/or radiographic outcome parameters of periodontal regenerative procedures OF DFDBA with other regenerative materials with a follow-up of more than 3 months were systematically assessed. PRISMA checklist was followed and electronic and hand search was done to identify the studies. Outcome variables were pocket probing depth and pocket depth reduction (PDR), clinical attachment level and clinical attachment gain (CAG), gingival recession (GR), bone fill and percentage (%) of bone fill. Meta-analysis was carried out with possible RCT studies using the DerSimonian–Laird estimator of variance. As sensitivity analysis, fixed-effect meta-analysis was performed using the Mantel–Haenszel method. The search resulted in 1235 published studies. After removal of duplicates and full-text analysis, 10 RCTs and 4 non-RCTs were selected. Overall, the result demonstrated the promising regenerative capacity of DFDBA with other graft materials for the treatment of intabony periodontal defect. Within the limitations of the present systematic review and meta-analysis, the use of DFDBA gives better results in terms of PDR, GR, bone fill, and percentage of bone fill when compared to other regenerative materials in treatment of intrabony periodontal defects, except CAG.